Mediating the relationship between talent management practices and intention to quit - Ncube, Chrisbel Mduduzi (My University, 2016)
Since McKinsey and Company (1998) coined the term “the war for talent” (Axelrod, Handfield-Jones, & Welsh, 2001; Michaels, Handfield-Jones & Axelrod, 2001) in response to a lack of highly skilled and talented employees in the labour market and the need for organisations to compete for this limited talent pool, the topic of talent management has received a remarkable degree of practitioner and academic interest (Bhatnagar, 2007; Collings & Mellahi, 2009; Vaiman, Scullion & Collings, 2012). The scarcity of highly skilled and talented employees has resulted in a paradigm shift, with the “old reality” (people need companies) replaced by new business realities (companies need talented and highly skilled people). This has forced organisations to institute aggressive talent management policies, practices and strategies to attract, develop, and optimise the available talent in both the broader market place and specific industries. The effective management of highly skilled and talented employees has also emerged as a major source of competitive advantage for organisations, resulting in desirable consequences such as organisational commitment, employee engagement, job satisfaction, and lower turnover intentions. Based on this premise, this study sought to investigate the direct and indirect (mediated) relationship between employees’ perception of the organisation’s current talent management practices, organisational commitment, employee engagement, job satisfaction and their intention to quit the organisation. The mediating characteristics of organisational commitment, employee engagement, and job satisfaction on the relationship between the perceived talent management practices and employees’ intention to quit are also investigated. A cross-sectional, survey-based descriptive research design utilising quantitative research methods was adopted to acquire information and primary data needed for analysis. The study was carried out on highly skilled and talented employees (supervisors, line managers, senior managers and directors) of a multinational fast moving consumer goods (FMCG) food manufacturing company in South Africa. The target population of the research comprised of (N = 267) 267 employees of the surveyed organisation with a sample size of (N = 151) 151 respondents. A standardised questionnaire adapted from five instruments ̶ talent management practices (Human Capital Institute, 2008), organisational commitment (Allen & Meyer, 1990), employee engagement (Schaufeli & Bakker, 2003), job satisfaction (Weiss, Dawis, England, & Lofquist, 1967), and intention to quit (Arnold & Feldman, 1982) measured on a Likert type of scale was utilised to collect primary data. A non-probability sampling technique (convenience sampling) was used to collect primary data. The scales used in the study reported Cronbach Coefficient Alphas above the minimum recommended 0.70 margin (Field, 2009) suggesting that the measuring instrument is reliable. The study utilised multiple linear regression analysis to test the proposed hypotheses. The results showed direct significant relationships between the variables under study, suggesting that investing in effective talent management practices relating to talent acquisition, workforce planning, talent development, performance management, talent retention, and other practices may result in desirable outcomes for the organisation. These include enhanced organisational commitment, high levels of employee engagement, increased employee job satisfaction, and reduced turnover intentions. It is recommended that organisations in South Africa and the organisation under study, in particular, develop talent management practices and strategies that can be implemented and applied in the organisation in order to attract and retain highly skilled and talented employees. It is further recommended that organisations develop effective, practical and holistic talent management practices and strategies that will not only attract talent, but also address organisational commitment, employee engagement, job satisfaction, and the retention of highly skilled and talented employees, thus boosting organisational performance and productivity.
A dissertation submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Commerce. Johannesburg, South Africa, May 2016
Keywords: Personnel management--South Africa; Employee retention--South Africa; Job satisfaction--South Africa; Organizational commitment--South Africa